2022
DOI: 10.1155/2022/8787782
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers for Ryanodine Receptor 1 (RYR1) Mutation-Associated Myopathies Using Bioinformatics Approach

Abstract: Background. Myopathies related to Ryanodine receptor 1 (RYR1) mutation are the most common nondystrophy muscle disorder in humans. Early detection and diagnosis of RYR1 mutation-associated myopathies may lead to more timely treatment of patients, which contributes to the management and preparation for malignant hyperthermia. However, diagnosis of RYR1 mutation-associated myopathies is delayed and challenging. The absence of diagnostic morphological features in muscle biopsy does not rule out the possibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Age, sex, fitness, and fibre type will all influence transcriptomic profiles in addition to the underlying genetic defects. Nevertheless, the integration of genome sequencing, transcriptomics, and bioinformatics data should prove fruitful to further our understanding of complex phenotypes [ 55 ], and predicting potential biomarkers in relation to RYR1-associated disease [ 56 ]. Whilst protein studies are needed to follow up observed transcriptional differences, and their full implications with respect to pathological processes remain to be explored, this study has confirmed the importance of mitochondrial metabolism in MH.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, fitness, and fibre type will all influence transcriptomic profiles in addition to the underlying genetic defects. Nevertheless, the integration of genome sequencing, transcriptomics, and bioinformatics data should prove fruitful to further our understanding of complex phenotypes [ 55 ], and predicting potential biomarkers in relation to RYR1-associated disease [ 56 ]. Whilst protein studies are needed to follow up observed transcriptional differences, and their full implications with respect to pathological processes remain to be explored, this study has confirmed the importance of mitochondrial metabolism in MH.…”
Section: Discussionmentioning
confidence: 99%
“…Although MYH1 has not been clearly associated to date with RYR1 -related myopathies, MYH1 mutations were associated with non-exertional rhabdomyolysis phenotype in horses 40 and MYH1 was recently considered a candidate gene for recurrent rhabdomyolysis also in humans 41 . Interestingly, the proteomic study of Eckhardt et al 42 showed a quantitative reduction of MYH1 in a mouse model with biallelic RYR1 mutations; accordingly, Wang et al 43 showed a significant reduction of MYH1 expression in muscle tissue from RYR1 mutated patients and suggested MYH1 as potential biomarkers for RYR1- myopathies. These data, together with the found interaction with CCDC78, reinforce the hypothesis of an intimate role of MYH1 with other SR proteins.…”
Section: Discussionmentioning
confidence: 99%